2020
DOI: 10.1038/s41467-020-16354-x
|View full text |Cite
|
Sign up to set email alerts
|

A genome-scale map of DNA methylation turnover identifies site-specific dependencies of DNMT and TET activity

Abstract: DNA methylation is considered a stable epigenetic mark, yet methylation patterns can vary during differentiation and in diseases such as cancer. Local levels of DNA methylation result from opposing enzymatic activities, the rates of which remain largely unknown. Here we developed a theoretical and experimental framework enabling us to infer methylation and demethylation rates at 860,404 CpGs in mouse embryonic stem cells. We find that enzymatic rates can vary as much as two orders of magnitude between CpGs wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
109
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(116 citation statements)
references
References 124 publications
7
109
0
Order By: Relevance
“…These sites also show tissue-specific variability of DNA methylation and display altered methylation patterns in many diseases ( 3 , 8 , 17–20 ). These observations suggest that pathways that recruit de novo methylation vary from cell type to cell type and that the genome-wide methylation patterns are a composite picture resulting from combined activity of multiple DNMT-targeting mechanisms and mechanisms that actively or passively remove methylation ( 21 ). In previous work, we and others have shown that the de novo DNMTs associate with genomic regions that are marked by distinct chromatin modifications, resulting in enhanced deposition of methyl marks at these sites.…”
Section: Introductionmentioning
confidence: 99%
“…These sites also show tissue-specific variability of DNA methylation and display altered methylation patterns in many diseases ( 3 , 8 , 17–20 ). These observations suggest that pathways that recruit de novo methylation vary from cell type to cell type and that the genome-wide methylation patterns are a composite picture resulting from combined activity of multiple DNMT-targeting mechanisms and mechanisms that actively or passively remove methylation ( 21 ). In previous work, we and others have shown that the de novo DNMTs associate with genomic regions that are marked by distinct chromatin modifications, resulting in enhanced deposition of methyl marks at these sites.…”
Section: Introductionmentioning
confidence: 99%
“…To further test if the observed difference could be influenced by the genomic context or different library representation of the queried sequences, we re-calculated the methylation scores only on the same CpGpNs that were covered in both, the TKO-DNMT3A2 and the TKO-DNMT3B libraries (Supplementary Figure 1d), and also on CpGpNs that were at least 80% methylated in wild type ES cells (Supplementary Figure 1e). The latter was necessary to exclude that active promoters and enhancers with elevated levels of DNA methylation turnover due to active DNA de-methylation (3, 4, 38) could have a potential influence on the calculated methylation scores. In both cases, the same sequence preference was observed when using these refined CpG sites (Supplementary Figure 1d-e), suggesting that different sequence composition in the WGBS libraries or genomics localisation is not the cause for the observed differences.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, female cells turned out to be more sensitive to the long-term effects of MEK inhibition, consistent with the expression of MEK inhibitory factors from the two active X chromosomes. Transcriptional mechanisms have been proposed to connect MEK-inhibition with DNA demethylation, specifically through upregulation of PRDM14, a transcriptional repressor of the DNA methyl-transferase DNMT3 gene family, and activity of the Tet-family of dioxygenases [ 83 , 84 , 86 , 87 , 90 ].
Fig.
…”
Section: Dna Methylation Separates Cdk8/19i From 2imentioning
confidence: 99%